2020
DOI: 10.1371/journal.pone.0226846
|View full text |Cite
|
Sign up to set email alerts
|

Age and altitude of residence determine anemia prevalence in Peruvian 6 to 35 months old children

Abstract: Background A Demographic and Family Health Survey (ENDES, for Encuesta Demográ fica y de Salud Familiar in Spanish) is carried out annually in Peru. Based on it, the anemia prevalence was 43.6% in 2016 and 43.8% in 2017 using the WHO cutoff value of 11 g/dL and the altitudecorrection equation. Objective To assess factors contributing to anemia and to determine its prevalence in Peruvian children 6 to 35 months old. Methods We used the MEASURE DHS-based ENDES survey to obtain representative data for11364 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 55 publications
3
26
0
4
Order By: Relevance
“…This age‐related pattern of an increase in Hb concentration, independent of altitude, was observed in a subsample of PSC with normal nutrition and higher SES. The data indicated that Hb concentration at any altitude is lower at 6–11, intermediate at 12–35, and higher at 36–59 months, which is consistent with the earlier reports 4,5,9,29,30 …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This age‐related pattern of an increase in Hb concentration, independent of altitude, was observed in a subsample of PSC with normal nutrition and higher SES. The data indicated that Hb concentration at any altitude is lower at 6–11, intermediate at 12–35, and higher at 36–59 months, which is consistent with the earlier reports 4,5,9,29,30 …”
Section: Discussionsupporting
confidence: 91%
“…The WHO recommendation to use an Hb value <11 g/dL for diagnosis of anemia in children aged 6–59 months does not account for these physiological changes. It has been suggested that the higher prevalence of apparent anemia in children aged 6–35 months is more because of the normal decrease in postpartum Hb, which may fall below the cutoff point of 11 g/dL, than to actual anemia 30 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since nearly half of Peru’s children under 5 are anaemic there is scope to include it in future work if we are looking for a holistic measure of the double burden. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that other problematic aspects of nutritional status, such as anaemia, persist, and are not reflected in our analysis. Since nearly half of Peru's children under 5 are anaemic there is scope to include it in future work if we are looking for a holistic measure of the double burden [40].…”
Section: Strengths and Limitationsmentioning
confidence: 99%